Ruta aviturística del cantón Pangua, provincia de Cotopaxi - Salazar Guanochanga, Dayana Mishel (2023)
The Canton Pangua has one urban parish and three rural ones, which due to the necessary distance to arrive them, they have several limitations, one of them is the information lack and tourism development; they have been developed tourist routes, despite the authorities disinterest, but it has not been considered bird watching, nor the birds as an important elementfor tourist activity to be them part. Therefore, it was considered the design a tourist route to take advantage of potential, what has the canton. It was developed a study area diagnosis, through bibliographic review, surveys, and interviews that they allowed to know, what the canton has an 1,000 meters altitudinal range above sea level at 3500 m,s,n,m, as well as the 14 places existence, where could be done bird watching; it was analyzed the proximity between sites, accessibility, roads, tourist plant, altitudinal range and climatic conditions to discriminate, technical manner, the sites, what will make up the route. It was defined 6 places, what are located in the four parishes from canton (El Corazón, Moraspungo, Pinllopata and Ramón Campaña). Therefore, it was considered the tourist route design to take advantage of potential,what has the canton. It was developed, through 7 field trips to the different established places, and by means direct observation with photographic record, it was got the birds inventory with 29 species total, they distributed in 11 orders and 18 families, each one with its taxonomic record, which includes its conservation status, according to the IUCN (all least concern). For verifying the sites suitability, it was applied the Sorensen index that allows determining the species similarity level between the study areas, they were considered the parishes as areas forperforming the calculation, getting what of the 6 possibles combinations, 4 are less 50% and only 2 are over 50%, by being the highest between zone 2 and 4 with 61%. Finally, the route was conceived with 6 bird observation points and 3 technical stops; it was opted for give the full day option; which lasts 24 hours, and that of two days one night with a 48 hours duration. The costs were considered with the all- inclusive package (accommodation, food, transportation, national or specialized guide, entrance fees); the cost varies depending onto theservice type to include, it can give the option by excluding the tour guide or to select betweeno national guide and a specialized guide. The current project demonstrates, what there is the possibility from making birdwatching activities in the canton, but for this, it is the possibility from making birdwatching activities in the canton, but for this, it is necessary to make a marketing plan for the route promotion, dissemination and commercialization designed in the current project